A new species of Coleophora (Lepidoptera: Coleophoridae: Coleophorinae) from the Galápagos Islands, Ecuador - Landry, Jean-François (Zootaxa, 2006)
Coleophora darwini sp. nov., is described from the Galápagos Islands. This is the first record of the family Coleophoridae for the Galápagos. Adults were reared from larvae found mining leaves of Amaranthus andersonii Howell (Amaranthaceae) on Pinzón Island. Adults of the species also were collected at light on the islands of Española and Pinta. Coleophora darwini is similar to C. intexta Meyrick, 1917 from Peru. Adults, and male and female genitalia of both species, as well as the larval case of C. darwini, are illustrated and morphological characters distinguishing the two species are presented. A lectotype is formally designated for C. intexta.